A Case Study: The Development of Calligraphy Education in Yogyakarta Indonesia - Ismail, Ahmad; Huda, Nurul; Anwari, M. Kanif; Hassan, Abd Rauf Tan Sri (Jurnal Pendidikan Islam, 2021)
This study aims to analyze the development and determine the perspective of calligraphy education in Yogyakarta. This research uses a qualitative approach with case studies to obtain a deep and comprehensive understanding of a phenomenon experienced by the research subject. The results showed that the development of calligraphy education was seen at three points of concentration; first, Islamic Higher Education (PTAI); second, in Islamic boarding schools or Islamic-based schools, as one of the learning curriculum materials for students; third; non-institutional calligraphy coaching. This study also contributes to an overview of the dynamics of the development of contemporary Islamic calligraphy in Yogyakarta. It appears a long process passed towards a work that can be enjoyed and deserves to be appreciated.